Analysis of Amilum Containment in Tomat Leaves (Solanum lycopersicum) Based on The Sach Test - Sanjayanti, Arum; Putri, Nurul Lia; Adawiyah, Khumairoh; Rammanda Putri, Bella Vista (Universitas Sembilanbelas November Kolaka, 2024)
Photosynthesis is the process of preparing organic substances H2O and CO2 into complex organic compounds that require light. Photosynthesis can only occur in plants that have chlorophyll, a pigment that functions as a catcher of sunlight energy which will later be converted into amylum. Amylum as a complex carbohydrate resulting from photosynthesis, plays an important role in various important physiological processes in the leaves. The purpose of this study was to determine the amylum content in tomato (Solanum lycopersicum) leaves. Qualitative descriptive method was carried out by referring to Sach's method by measuring the starch content of leaves using foil and betadine (Iodine) on tomato leaf samples. The results showed the presence of amylum in tomato leaves that were not covered with aluminum foil after being tested with Iodine solution. This is evidenced by the change in leaf color to blue-black on the surface of the leaves. While in tomato leaves covered with aluminum foil the color of the leaves turns pale and there are only a few blue-black spots, this indicates that leaves that are not exposed to direct sunlight and do not undergo photosynthesis normally have little amylum content in them. Keywords: Amylum, Solanum lycopersicum, Sach Test